Peran Pemerintah Yogyakarta dalam Mengembangkan Pelaku UMKM Melalui SiBakul Jogja - Faqih Muqoddam Alchudhory; Zulkipli Lessy (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Micro, small and medium enterprises (MSMEs) are facing huge challenges in adapting and surviving after the Covid-19 pandemic. The role of government is key in providing support and appropriate policies to help MSMEs. This study examines the role of the Yogyakarta government in facilitating the post-pandemic adjustment of MSMEs and analyzes various factors that affect MSME survival. These factors include the decline in MSME income and how the government's role can help increase it, limited resources and access to financing, innovation in business, and community and government support. Through literature studies and interviews with MSME actors, this research concludes that with the right support, MSMEs can overcome post-pandemic challenges and grow sustainably.